Pediatric Chronic Critical Illness, Prolonged ICU Admissions, and Clinician Distress - Miles, Alison H.; Rushton, Cynda H.; Wise, Brian M.; Moore, Aka; Boss, Renee D. (Journal of Pediatric Intensive Care, 2021)
To gain an in-depth understanding of the experience of pediatric intensive care unit (PICU) clinicians caring for children with chronic critical illness (CCI), we conducted, audiotaped, and transcribed in-person interviews with PICU clinicians. We used purposive sampling to identify five PICU patients who died following long admissions, whose care generated substantial staff distress. We recruited four to six interdisciplinary clinicians per patient who had frequent clinical interactions with the patient/family for interviews. Conventional content analysis was applied to the transcripts resulting in the emergence of five themes: nonbeneficial treatment; who is driving care? Elusive goals of care, compromised personhood, and suffering. Interventions directed at increasing consensus, clarifying goals of care, developing systems allowing children with CCI to be cared for outside of the ICU, and improving communication may help to ameliorate this distress.
Keywords: pediatric intensive care units; chronic critical illness; heath teams; interdisciplinary; palliative care; communication